Real exchange rate and international reserves in the era of growing financial and trade integration - Aizenman, Joshua 1949-; Riera-Crichton, Daniel (National Bureau of Economic Research, 2006)
This paper evaluates the impact of international reserves, terms of trade shocks and capital flows on the real exchange rate (REER). We observe that international reserves cushions the impact of TOT shocks on the REER, and that this effect is important for developing but not for industrial countries. This buffer effect is especially significant for Asian countries, and for countries exporting natural resources. Financial depth reduces the buffer role of IR in developing countries. Developing countries REER seem to be more sensitive to changes in reserve assets; whereas industrial countries display a significant relationship between hot money and REER.
Literaturverz. S. 12 - 13